Reconocimiento de metáforas de literatura en niños escolares - Pineda, Patricia (Colombian Applied Linguistics Journal, 2018)
Given the need to advance in the understanding of the recognition of metaphorical uses by schoolchildren from a psycholinguistic perspective of language in use that goes beyond the perspective of developmental psychology, this article presents the results of a study about metaphor recognition by children. The premise is that the linguistic metaphor is a phenomenon of language use and that the analysis of its processing has to take into account the processes of textual comprehension. The linguistic material was taken from children’s literature and participants were asked to underline metaphors. Statistical analysis was made using ANOVA with two inter-subject factors (reading comprehension and school grade). The results indicate advances in metaphorical recognition with school grade and level of reading comprehension and a significant influence of the latter, exceeding in some cases that of the school grade; as well as important differences in performance of children with the same level of reading comprehension. These findings provide evidence about the relevance of reading comprehension but also stress the importance to better identify the role of the different sub-skills involved in reading comprehension in metaphor recognition.